2018
DOI: 10.1016/j.jenvman.2017.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Toilet revolution in China

Abstract: The wide-spread prevalence of unimproved sanitation technologies has been a major cause of concern for the environment and public health, and China is no exception to this. Towards the sanitation issue, toilet revolution has become a buzzword in China recently. This paper elaborates the backgrounds, connotations, and actions of the toilet revolution in China. The toilet revolution aims to create sanitation infrastructure and public services that work for everyone and that turn waste into value. Opportunities f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 42 publications
0
128
0
2
Order By: Relevance
“…The authors pointed out that several sanitation technologies in the study area were constituted of septic tanks, traditional pit latrines, ventilated improved pit latrines and piped equipped latrines. Indeed, the results of Cheng et al (2018) working on the toilet revolution in China revealed several methods of improved sanitation technologies which are represented by septic tanks, doublevault funnel latrine, double pit alternate type, biogas-linked toilet, urine-faeces diversion latrine and integrated flushing latrine. In addition, the finding Stenström et al (2011) who assessed microbial exposure and health assessments in sanitation technologies and systems in tropical area found that open defecation is widespread in developing countries and is the most significant environmental factor involved in the transmission of sanitation-related diseases.…”
Section: Typology Of On-site Sanitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors pointed out that several sanitation technologies in the study area were constituted of septic tanks, traditional pit latrines, ventilated improved pit latrines and piped equipped latrines. Indeed, the results of Cheng et al (2018) working on the toilet revolution in China revealed several methods of improved sanitation technologies which are represented by septic tanks, doublevault funnel latrine, double pit alternate type, biogas-linked toilet, urine-faeces diversion latrine and integrated flushing latrine. In addition, the finding Stenström et al (2011) who assessed microbial exposure and health assessments in sanitation technologies and systems in tropical area found that open defecation is widespread in developing countries and is the most significant environmental factor involved in the transmission of sanitation-related diseases.…”
Section: Typology Of On-site Sanitationmentioning
confidence: 99%
“…According to the literature, the number of latrine users could strongly affect the rate of faecal sludge accumulation in the pits of latrines as the excreta production rate per person was estimated at about 0.12 to 0.40 litre of faeces and 0.6 to 1.5 litre of urine per day (Bakare et al, 2012). In addition, the work of Cheng et al (2018) pointed out about a million tons of faecal sludge collected yearly in public toilet in urban area of China. Furthermore the study done by Gning et al (2017) in Dakar pointed out the absence of regulations by the Senegal Government in term of the cost of desludging paid by households for having access to the mechanical emptying service.…”
Section: Latrine Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, the Chinese government allocated 7 billion RMB in upgrading rural toilet facilities [14]. The Chinese government actively supported the concept of a 'Toilet Revolution' originally proposed by UNICEF in 1997 [15]. China is a major industrialised country and most probably has the largest squatting toilet market in the world [15].…”
Section: Resultsmentioning
confidence: 99%
“…In UDDT systems, feces and urine are collected separately; the urine can be diluted along with water and used as fertilizer directly, while feces are dewatered for and treated to destroy pathogens. Human excrement from this process can be used for biogas production, which is used mainly for cooking and lighting (Cheng et al., ; Simha et al., ). This toilet system is based on a technology, which has been in application for many years in some developing and developed countries, such as United States of America and China, and has been subsequently improved with a resource‐recovery approach as an important feature (Cheng et al., ).…”
Section: Appropriate Sanitation System Developmentmentioning
confidence: 99%